A Review of In-Situ Techniques for Probing Active Sites and Mechanisms of Electrocatalytic Oxygen Reduction Reactions - Zhao, Jinyu; Lian, Jie; Zhao, Zhenxin; Wang, Xiaomin; Zhang, Jiujun (Nano-Micro Letters, 2022)
Electrocatalytic oxygen reduction reaction (ORR) is one of the most important reactions in electrochemical energy technologies such as fuel cells and metal–O2/air batteries, etc. However, the essential catalysts to overcome its slow reaction kinetic always undergo a complex dynamic evolution in the actual catalytic process, and the concomitant intermediates and catalytic products also occur continuous conversion and reconstruction. This makes them difficult to be accurately captured, making the identification of ORR active sites and the elucidation of ORR mechanisms difficult. Thus, it is necessary to use extensive in-situ characterization techniques to proceed the real-time monitoring of the catalyst structure and the evolution state of intermediates and products during ORR. This work reviews the major advances in the use of various in-situ techniques to characterize the catalytic processes of various catalysts. Specifically, the catalyst structure evolutions revealed directly by in-situ techniques are systematically summarized, such as phase, valence, electronic transfer, coordination, and spin states varies. In-situ revelation of intermediate adsorption/desorption behavior, and the real-time monitoring of the product nucleation, growth, and reconstruction evolution are equally emphasized in the discussion. Other interference factors, as well as in-situ signal assignment with the aid of theoretical calculations, are also covered. Finally, some major challenges and prospects of in-situ techniques for future catalysts research in the ORR process are proposed. Highlights: 1 A comprehensive discussion of monitoring the structure evolutions of catalysts during ORR via multiple in-situ techniques to identify the active sites is presented. 2 The extensive applications of in-situ techniques in elucidating the oxygen reduction reaction (ORR) mechanisms/pathways are reviewed. 3 The challenges and recommendations of current in-situ techniques for monitoring the various dynamic evolutions in ORR are pointed out.